Encaged and Enraged: a Study of How Level of Aggression Relates to Perceived Crowdedness, Risk, and Boredom - Lo, Lap Yan (International journal of conflict and violence, 2023)
Social distancing policies have been practiced in different regions around the world to minimize the number of cases of COVID-19. After an outbreak in mid-July 2020, the Hong Kong government adopted a series of administrative measures and strongly encouraged residents to stay at home. This lockdown period provided an opportunity to study variations in levels of aggression when people spend more time than usual in an overcrowded living environment. A total of 185 Hong Kong residents were recruited for this study. Their perceptions of the crowdedness of their living space, aggression level (measured using the BPAQ-SF), proneness to boredom (measured by the BFS-SF), and perceptions of risk regarding COVID-19 were collected via online questionnaires. Perceived crowdedness, proneness to boredom, and perceptions of susceptibility to COVID-19 were found to significantly predict the variance of different types of aggression in a regression model. In a mediation analysis, anger acted as a mediator of the relationship between proneness to boredom and different types of aggression. Participants’ perceptions of their susceptibility to COVID-19 suggested an underlying worry about the contagiousness of the virus, which was in turn associated with feelings of uncertainty and a rise in aggression level.